2018
DOI: 10.1111/cns.13059
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinate‐curcumin ameliorates cognitive impairment in diabetic rats by rescuing autophagic flux in CA1 hippocampus

Abstract: These results indicate that NC ameliorates DM-induced cognitive function impairment via restoring autophagic flux might by inhibiting mTOR/p70S6k activation in the CA1 region, and NC may be a promising agent for diabetic cognitive dysfunction prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…Ischemic lesion volume is an important predictor of functional outcome after stroke with larger lesions corresponding to worse stroke outcome 43,44 . Diabetes and stroke are both known to trigger neuronal apoptosis, and dysregulated apoptosis in the IBZ can contribute to increased cell death and larger infarct area following stroke 44–46 . Ang1 has previously been shown to reduce infarct volume in mice subjected to focal cerebral embolic ischemia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic lesion volume is an important predictor of functional outcome after stroke with larger lesions corresponding to worse stroke outcome 43,44 . Diabetes and stroke are both known to trigger neuronal apoptosis, and dysregulated apoptosis in the IBZ can contribute to increased cell death and larger infarct area following stroke 44–46 . Ang1 has previously been shown to reduce infarct volume in mice subjected to focal cerebral embolic ischemia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced autophagy in the hippocampus is reportedly able to improve cognitive impairment in rats . AMPKα1‐induced autophagy is a key mechanism for minocycline to protect neurons from radiation‐induced apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinate-curcumin is a novel derivative of nicotinate and curcumin, with improved water solubility and bioavailability [ 11 ]. Recent studies have reported that NC not only induces HCT116, MCF-7, and CNE2 cell apoptosis and cycle arrest through a P53-mediated mechanism in cancer, but also ameliorates cognitive impairment in diabetic rats [ 23 , 24 ]. Furthermore, NC regulates lipid metabolism, impedes foam cell formation, and inhibits atherosclerosis formation in apoE −/- mice with vascular diseases [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%